1992
DOI: 10.1029/91jd02831
|View full text |Cite
|
Sign up to set email alerts
|

Atmosphere‐surface exchange of mercury in a forest: Results of modeling and gradient approaches

Abstract: We have modified recently published dry deposition models to estimate deposition velocities (Vd) for Hg in both fine aerosol and vapor form to forest canopy surfaces. Aerosol and total vapor phase Hg concentrations in air previously measured at Walker Branch Watershed in Tennessee have been used with model results to estimate dry deposition to a deciduous forest. The concentration data confirm that airborne Hg is dominated by vapor forms at this site and exhibits concentrations moderately above continental bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
78
1
5

Year Published

1998
1998
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 210 publications
(93 citation statements)
references
References 32 publications
9
78
1
5
Order By: Relevance
“…van Hove et al, 2002) and it lacks representation of canopy emission of GEM Lindberg and Meyers 2001;. Xu et al (1999) side-stepped modeling a compensation point by separately calculating GEM deposition according to Lindberg et al (1992) and formulating a separate model for canopy emission of GEM consistent with the very limited (pre-1999) understanding of controls on this process. Net GEM deposition was taken to be the net of the two model results.…”
Section: Cloud-water Depositionmentioning
confidence: 99%
See 3 more Smart Citations
“…van Hove et al, 2002) and it lacks representation of canopy emission of GEM Lindberg and Meyers 2001;. Xu et al (1999) side-stepped modeling a compensation point by separately calculating GEM deposition according to Lindberg et al (1992) and formulating a separate model for canopy emission of GEM consistent with the very limited (pre-1999) understanding of controls on this process. Net GEM deposition was taken to be the net of the two model results.…”
Section: Cloud-water Depositionmentioning
confidence: 99%
“…Recent measurements of GEM emission from vascular plant canopies suggest that some biological process (bioreduction) at the root-soil interface may be responsible for the production of and apparent supersaturation of Hg 0 in the xylem of plants exhibiting net GEM emission . Rea et al (2002) measured mercury in the foliage of deciduous trees over the course of the growing season and found that total foliar mercury accumulation was substantially less than GEM deposition estimated following Lindberg et al (1992). Rea et al (2001) determined that Hg p and RGM dry deposition are rapidly washed off foliar surfaces, and, therefore, foliar accumulation of mercury most likely represents GEM assimilation.…”
Section: Cloud-water Depositionmentioning
confidence: 99%
See 2 more Smart Citations
“…These fluxes between the terrestrial vegetation and the atmosphere impact micro and mesoscale meteorology, regional and global climate change, carbon balance and cycling, as well as hydrology. 1, 2 Fluxes of trace gases and aerosols at the canopyatmosphere interface also determine the important role of vegetated surfaces on the removal of air pollutants (e.g., tropospheric ozone, 3, 4 heavy metals, 5 and aerosols 6 ). Transport of biogenic particles emitted from forests and crops such as pollens, 7 seeds, 8 and spores 9 also play an important role in ecological and agricultural processes.…”
Section: Introductionmentioning
confidence: 99%